Radiological analysis of large and aggressive mandibular ossifying fibroma in panoramic radiograph: A case report - Wulansari, Dwi P.; Rahman, Fadhlil UA. (Hasanuddin University, 2024)
Objective: This case report aimed to explain the specific radiological features and interpretation of the finding of a mixed radiolucent-radiopaque lesion in the mandible, which was subsequently suspected to be an ossifying fibroma and was confirmed histopathologically according to the results of the radiological interpretation. Methods: A 25-year-old man was referred to the oral maxillofacial radiology unit of Hasanuddin University Dental Hospital with a chief complaint of facial asymmetry caused by enlargement in the left mandibular region without pain. Extra oral examination showed an asymmetrical face caused by enlargement in the left mandibular with no crepitus or pain on palpation. Intra-oral examination revealed swelling on the lower left buccal vestibule of the first premolar to the second molar with mobility in the lower left second molar.Results: The patient underwent a panoramic radiography examination, with the results of radiological interpretation showing the presence of well-defined mixed radiolucent-radiopaque lesions in the left mandibular from mesial lower left canine extended to the distal of the third molar. The effect of the lesion also shows the mandibular bone expansion involving the inferior cortex of the mandible.Conclusion: Ossifying fibroma is more common in the mandible, frequently has a mixed radiographic appearance, and tends to grow into large size, resulting in facial disfigurement. Correlation between clinical, imaging, and histopathological features is essential for establishing a proper diagnosis.